Effect of starch level in supplement with or without oil source on diet and apparent digestibility, rumen fermentation and microbial population of Nellore steers grazing tropical grass - Neto, Antonio Jose [UNESP]; Messana, Juliana D. [UNESP]; Granja-Salcedo, Yury T. [UNESP]; Castagnino, Pablo S. [UNESP]; Fiorentini, Giovani [UNESP]; Reis, Ricardo A. [UNESP]; Berchielli, Telma T. [UNESP] (Elsevier, 2017)
In this study, we evaluated the effects of starch level in supplement, with/without whole soybean (oil source), on diet intake and apparent digestibility, rumen microbial population, and fermentation parameters in Nellore steers grazing Brachiaria brizantha cultivar Xaraés during the finishing phase. Eight ruminal cannulated Nellore steers (514 kg ± 30) were used in a replicate 4 × 4 Latin square with a 2 × 2 factorial arrangement of treatments. The diets used had different levels of supplemented starch [corn (high) or soybean hulls (SH: low)] with/without a source of oil (soybean grain). There were no interactions between starch level and oil in supplements on the intake of DM (% of body weight, P = 0.602; kg/d, P = 0.703), forage DM (P = 0.630), supplement DM (P = 0.501), OM (P = 0.669), CP (P = 0.420), aNDFom (P = 0.380), EE (P = 0.199) and GE (P = 0.620). However, intake and total apparent digestibility of DM, OM, and aNDFom (P < 0.050) decreased with oil supplementation, whereas the intake and digestibility of aNDFom were increased (P < 0.010) with low-starch supplementation. There were no interactions between starch supplement and oil source supplementation for pH (P = 0.391), NH3-N (P = 0.473), and total volatile fatty acids (P = 0.441). The inclusion of an oil source in supplements decreased (P < 0.010) the acetate concentration in the rumen when compared with supplements without oil, independent of starch level. Supplementation with high-starch increased the numbers of Entodinium (P < 0.010), and total protozoa (P < 0.010). Furthermore, independently of starch level, the addition of an oil source decreased the population of Dasytricha (P < 0.010), Polyplastron (P < 0.010), and Diploplastron (P = 0.040). Supplementing animals with low-starch (SH) without oil resulted in a higher proportion of Ruminococcus albus (P = 0.012) compared with the other supplements. Moreover, low-starch (SH) supplement, with or without oil, decreased the relative population of Selenomonas ruminantium (P = 0.003). The addition of oil in supplements decreased the number of Fibrobacter succinogenes (P < 0.001), Ruminococcus flavefasciens (P < 0.001), and Archeas (P < 0.001), but increased Anaerovibrio lipolytica populations (P < 0.001). Oil supplement decreased intake, digestibility, acetate production, protozoan populations, and fibrolytic rumen bacteria. The use of soybean hulls without whole soybean supplementation may be effective in increasing the digestibility of CP and R. albus in finishing Nellore steers grazing B. brizantha during the dry season.
Keywords: Bacteria; Digestion; Lipid; Microbial protein; Protozoa; Soybean hull